Testing Tele‐Savvy: Protocol for a randomized controlled trial. Issue 2 (5th February 2018) - Kovaleva, Mariya A.; Bilsborough, Elizabeth; Griffiths, Patricia C.; Nocera, Joe; Higgins, Melinda; Epps, Fayron; Kilgore, Katie; Lindauer, Allison; Morhardt, Darby; Shah, Raj C.; Hepburn, Kenneth
ABSTRACT: Many informal caregivers of persons with dementia suffer adverse health consequences. Although established psychoeducation programs are known to benefit caregivers, attending in‐person programs is challenging for them. To address this challenge, the Savvy Caregiver Program, an evidence‐based psychoeducation program with demonstrated effectiveness for caregiving and disease‐related outcomes, was transformed into an on‐line program, Tele‐Savvy. This article describes the rationale for and design of a prospective longitudinal randomized controlled trial (targeted N = 215), currently underway. The trial aims to establish Tele‐Savvy's efficacy in (i) reducing the negative effects of caregiving on caregivers; (ii) promoting care recipients' quality of life; (iii) improving caregiver mastery; and to explore (iv) Tele‐Savvy's efficacy among caregivers of different races/ethnicities. The mediating role of mastery will be assessed. Participants are randomized to the active condition (immediate Tele‐Savvy participation), attention control, or usual care. Participants in the two latter conditions will complete Tele‐Savvy 6 months post‐baseline. Multilevel mixed effects models will be used to examine changes in outcomes and to model group by time (months since baseline) interactions. The exploratory aim will be addressed using analysis of covariance and qualitative analysis. This trial's results may be used by healthcare and community organizations to implement Tele‐Savvy in dementia care, increasing caregivers' access to this evidence‐based intervention.